Work-Life Balance Challenges and Family-Friendly Policies: Evidence from Qatar - Julia Barbar (17963358) (2023)
This chapter focuses on the major challenges facing women in balancing work and family life, highlighting the crucial role of cultural and institutional factors in shaping work-life policies in Qatar. The chapter provides a comparative analysis of human resource laws and recent developments in family-friendly policies, such as leave, childcare, and flexible work arrangements. The chapter also presents the findings of 26 semi-structured interviews with local and migrant women, exploring the challenges they face in the workplace, the factors influencing their employment decisions, and the impact of the COVID-19 pandemic on their work-life experiences. The chapter concludes with insights into the significance of part-time work and flexible work arrangements for women in Qatar. Other Information Published in: Women's Empowerment and Public Policy in the Arab Gulf States : Exploring Challenges and Opportunities License: http://creativecommons.org/licenses/by/4.0/ See chapter on publisher's website: http://dx.doi.org/10.1007/978-981-99-6006-4_5